Genoprotective activity of the Pleurotus eryngii mushrooms following their in vitro and in vivo fermentation by fecal microbiota - Boulaka, Athina; Mantellou, Panagiota; Stanc, Gabriela-Monica; Souka, Efthymia; Valavanis, Christoς; Saxami, Georgia; Mitsou, Evdokia; Koutrotsios, Georgios; Zervakis, Georgios I.; Kyriacou, Adamantini; Pletsa, Vasiliki; Georgiadis, Panagiotis (Frontiers in Nutrition, 2022)
Pleurotus eryngii mushrooms are commercially cultivated and widely consumed due to their organoleptic properties, and the low caloric and high nutritional value. In addition, they contain various biologically active and health-promoting compounds; very recently, their genoprotective effect in Caco-2 cells after their fermentation by the human fecal microbiota was also documented. In the current study, the effect of P. eryngii pre- and post-fermentation supernatants in micronuclei formation was evaluated in human lymphocytes. In addition, the genoprotective properties of increasing concentrations of aqueous extracts from P. eryngii mushrooms (150, 300, 600 mg/kg) against the cyclophosphamide-induced DNA damage were studied in young and elderly female and male mice in bone marrow and whole blood cells. The ability of the highest dose (600 mg/kg) to regulate the main cellular signaling pathways was also evaluated in gut and liver tissues of female animals by quantifying the mRNA expression of NrF2, Nfkβ, DNMT1 and IL-22 genes. P. eryngii post-fermentation, but not pre-fermentation, supernatants were able to protect human lymphocytes from the mitomycin C-induced DNA damage in a dose-dependent manner. Similarly, genoprotection was also observed in bone marrow cells of mice treated by gavage with P. eryngii extract. The effect was observed in all the experimental groups of mice (young and elderly, male and female) and was more potent in young female mice. Overexpression of all genes examined was observed in both tissues, mainly among the elderly animals. In conclusion, P. eryngii mushrooms were shown to maintain genome integrity through protecting cells from genotoxic insults. These beneficial effects can be attributed to their antioxidant and immunomodulatory properties, as well as their ability to regulate the cell’s epigenetic mechanisms and maintain cell homeostasis.